Clinical Practice Recommendations on Genetic Testing of CYP2C9 and VKORC1 Variants in Warfarin Therapy. Issue 4 (August 2015) - Shaw, Kaitlyn; Amstutz, Ursula; Kim, Richard B.; Lesko, Lawrence J.; Turgeon, Jacques; Michaud, Veronique; Hwang, Soomi; Ito, Shinya; Ross, Colin; Carleton, Bruce C.
Abstract : Objective: To systematically review evidence on genetic variants influencing outcomes during warfarin therapy and provide practice recommendations addressing the key questions: (1) Should genetic testing be performed in patients with an indication for warfarin therapy to improve achievement of stable anticoagulation and reduce adverse effects? (2) Are there subgroups of patients who may benefit more from genetic testing compared with others? (3) How should patients with an indication for warfarin therapy be managed based on their genetic test results? Methods: A systematic literature search was performed for VKORC1 and CYP2C9 and their association with warfarin therapy. Evidence was critically appraised, and clinical practice recommendations were developed based on expert group consensus. Results: Testing of VKORC1 (−1639G>A), CYP2C9*2, and CYP2C9*3 should be considered for all patients, including pediatric patients, within the first 2 weeks of therapy or after a bleeding event. Testing for CYP2C9*5, *6, *8, or *11 and CYP4F2 (V433M) is currently not recommended. Testing should also be considered for all patients who are at increased risk of bleeding complications, who consistently show out-of-range international normalized ratios, or suffer adverse events while receiving warfarin. Genotyping results should be interpreted using a pharmacogenetic dosing algorithm to estimate the required dose. Significance: This review provides the latest update on genetic markers for warfarin therapy, clinical practice recommendations as a basis for informed decision making regarding the use of genotype-guided dosing in patients with an indication for warfarin therapy, and identifies knowledge gaps to guide future research. Abstract : Supplemental Digital Content is Available in the Text.